2021
DOI: 10.1002/jbt.22757
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated lnc‐HZ02 and miR‐hz02 inhibited migration and invasion by downregulating the FAK/SRC/PI3K/AKT pathway in BPDE‐treated trophoblast cells

Abstract: BPDE (benzo(a)pyren-7,8-dihydrodiol-9,10-epoxide), a metabolite of environmental carcinogenic BaP, weakens the migration and invasion of human villous trophoblast cells and may further induce miscarriage. However, the underlying mechanisms remain largely unknown. In this study, we identified that in trophoblast Swan 71 and HTR-8/SVneo cells, miR-hz02 upregulates the level of lnc-HZ02, which inhibits the expression of an RNA-binding protein HuR. HuR could interact with FAK mRNA and promote its mRNA stability, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…It has been reported that HuR is an RNA binding protein, which could bind RNAs containing AUUU specific sequence and enhance their RNA stability. 44 Here, we explored whether HuR protein could promote PLD1 mRNA stability in human trophoblast cells. We found that in both Swan 71 and HTR-8/SVneo cells, those with overexpression of HuR had higher, whereas those with HuR knockdown had lower PLD1 mRNA and protein levels ( Figure 2L ; S5C–F).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that HuR is an RNA binding protein, which could bind RNAs containing AUUU specific sequence and enhance their RNA stability. 44 Here, we explored whether HuR protein could promote PLD1 mRNA stability in human trophoblast cells. We found that in both Swan 71 and HTR-8/SVneo cells, those with overexpression of HuR had higher, whereas those with HuR knockdown had lower PLD1 mRNA and protein levels ( Figure 2L ; S5C–F).…”
Section: Resultsmentioning
confidence: 99%
“…Focal adhesion kinases (FAKs) are a class of cytoplasmic non-receptor protein tyrosine kinases that belong to the protein tyrosine kinase (PTK) superfamily and are therefore also known as PTK II (32). FAKs can integrate signals from integrins, growth factors and mechanical stimuli to activate intracellular PI3K/Akt, Ras/MAPK and other signaling pathways to regulate cell growth (33)(34)(35). Numerous studies on the association of FAKs with different types of cancers have shown a close link between FAKs and the biological mechanisms that promote cancer development and progression (36).…”
Section: Discussionmentioning
confidence: 99%
“…In our recent work, we have identified that inhibition in trophablast cell proliferation, migration/invasion or the increase in trophoblast cell apoptosis is associated with RM. [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ] However, whether other dysfunctions of human trophoblast cells might also induce miscarriage should be further explored.…”
Section: Introductionmentioning
confidence: 99%
“…[ 45 ] Recently, we have found that BPDE induced trophoblast apoptosis, ferroptosis, and pyroptosis, and also inhibited trophoblast migration/invasion and proliferation. [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 46 ] In animal studies, we found that BaP exposure induced miscarriage of pregnant mice. [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 46 ] However, it is still unclear whether BPDE might impair HR repair in human trophoblast cells and whether this impairment might further induce miscarriage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation